2014
DOI: 10.1021/om5002414
|View full text |Cite
|
Sign up to set email alerts
|

Partially and Fully Reversible Solvation-Controlled Borylene Swapping and Metal-Only Lewis Pair Formation

Abstract: New borylene-containing metal-only Lewis pairs based on group 6 metals and ruthenium are prepared by a partially reversible borylene transfer from group 6 borylene complexes [M{BN­(SiMe3)2}­(CO)5] (M = Mo, W). The complexes contain strong Ru → Mo/W dative interactions. As in a previous report on related compounds, redissolving these complexes resulted in reversion back to the precursors, enabled by a sacrificial CO donor. It was observed that this reversion process becomes less selective as the group 6 metal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The unique robustness and purely σ-donor nature of these M–B linkages (Figure , right) is highly reminiscent of NHC-metal complexes. Indeed, reaction of 2 with the cationic coinage metal species [(IDipp)­CuOTf] results in the formation of the “metal-only Lewis pair” (MOLP) species 6 (Scheme ), Figure ) where a Fe–Cu bond has been formed. This observation stands in contrast to known metalloborylene reactivity with coinage metals, where coordination to the borylene M–B π-bond has been described .…”
Section: Resultsmentioning
confidence: 99%
“…The unique robustness and purely σ-donor nature of these M–B linkages (Figure , right) is highly reminiscent of NHC-metal complexes. Indeed, reaction of 2 with the cationic coinage metal species [(IDipp)­CuOTf] results in the formation of the “metal-only Lewis pair” (MOLP) species 6 (Scheme ), Figure ) where a Fe–Cu bond has been formed. This observation stands in contrast to known metalloborylene reactivity with coinage metals, where coordination to the borylene M–B π-bond has been described .…”
Section: Resultsmentioning
confidence: 99%
“…This intrinsic electronic distinction between amino- and alkyl-/arylborylenes differentiates their chemical reactivity. Reactivity studies have shown that group 6 aminoborylenes serve as an excellent source for the borylene [:BR] fragment, which allows direct boron functionalization of both organic and organometallic substrates. , One particularly useful application of this chemistry is in the synthesis of new terminal and bridging borylene complexes. The first terminal bis­(borylene) [(η 5 -C 5 Me 5 )­Ir­{BN­(SiMe 3 ) 2 } 2 ] ( 2 ) was synthesized (Scheme , A ) by adding 2 equiv of the chromium aminoborylene complex [(OC) 5 CrBN­(SiMe 3 ) 2 ] ( 1 ) as a borylene source to 1 equiv of the iridium carbonyl complex [(η 5 -C 5 Me 5 )­Ir­(CO) 2 ] under photolytic conditions …”
Section: Bondingmentioning
confidence: 99%
“…When we began our work in this field, perhaps the most well-studied subset of MOLPs was that featuring zerovalent group 8 donors (M 0 L n , M = Fe, Ru, Os) and transition metal acceptors, thanks to extensive work by the groups of Pomeroy, Mak, and Dixneuf (and subsequently also Krossing). , However, MOLPs featuring zerovalent group 8 donors and simple main-group Lewis acids were at that time unknown. After our discovery that gallium trihalides form stable Lewis adducts with pentacoordinate Fe 0 complexes, we began a systematic study of MOLPs of the form [L n Fe 0 /L n Ru 0 →GaX 3 ]. , Using a range of different donor ligands bound to the group 8 metal centers, we were able to establish trends in the Lewis basicity of Fe 0 and Ru 0 complexes by comparisons of M–Ga bond distances, sums of X–Ga–X angles, and computationally derived bond dissociation energies.…”
Section: Introductionmentioning
confidence: 99%